2021
DOI: 10.1126/sciimmunol.abe4782
|View full text |Cite
|
Sign up to set email alerts
|

Severely ill patients with COVID-19 display impaired exhaustion features in SARS-CoV-2–reactive CD8 + T cells

Abstract: The molecular properties of CD8+ T cells that respond to SARS-CoV-2 infection are not fully known. Here, we report on the single-cell transcriptomes of >80,000 virus-reactive CD8+ T cells, obtained using a modified Antigen-Reactive T cell Enrichment (ARTE) assay, from 39 COVID-19 patients and 10 healthy subjects. COVID-19 patients segregated into two groups based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
192
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(211 citation statements)
references
References 114 publications
17
192
0
2
Order By: Relevance
“…The results of the differential expression analysis on raw counts (|log2 fold-change| > 0.25) are reported in Table S7. Gene signatures for cytotoxic, viral, unhelped, IFN-γ and exhaustion responses were obtained from Kusnadi et al (38), and enrichment was evaluated using R package AUCell (68).…”
Section: Tetramer Sorting Hashtag Labeling and Single-cell Rna Sequementioning
confidence: 99%
“…The results of the differential expression analysis on raw counts (|log2 fold-change| > 0.25) are reported in Table S7. Gene signatures for cytotoxic, viral, unhelped, IFN-γ and exhaustion responses were obtained from Kusnadi et al (38), and enrichment was evaluated using R package AUCell (68).…”
Section: Tetramer Sorting Hashtag Labeling and Single-cell Rna Sequementioning
confidence: 99%
“…Recent studies have mapped the host immune profiles associated with different stages along the COVID-19 disease trajectory. Reproducible immune correlates of severe COVID-19 include prolonged detection of proinflammatory cytokines such as IL-6, TNFα, and IL-8, diminished type I and type III interferon, and marked lymphopenia, as well as mixed evidence for immune exhaustion and dysfunctional myeloid populations 1725 . These reports have measured host inflammatory and immune signatures in peripheral blood, which may only partially reflect the immune status within virally targeted tissues 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly these cells exhibited lesser cytotoxic and inflammatory features and could maintain their exhausted state even after viral clearance. In contrast, SARS-CoV-2 reactive CD8 + T cells from patients with severe disease displayed multiple features that support the generation of robust CD8 + T cell memory responses with pro-survival properties and a lack of restraining exhaustion features [399]. To what degree SARS-CoV-2 causes T cell exhaustion and/or impaired T cell memory remains to be determined.…”
Section: The Time Course Of T Cell Responses In Sars-cov-2 and Hiv-1 Infectionmentioning
confidence: 99%
“…A longitudinal study of CD8 + T cells during SARS-CoV-2 infections revealed an exhausted phenotype of CD8 + T cells, based on the presence of exhaustion markers including PD-1, CTLA-4, and TIGIT, which, together with reduced poly-functionality according to markers such as IFN-γ, TNF-α, and IL-2 predicted disease severity [396]. However, other studies showed that CD8 + T cells are not exhausted but remain functional [397,398] and a significant proportion of SARS-CoV-2 reactive T cells with "exhausted" phenotype are also found in patients with mild COVID-19 [399]. Interestingly these cells exhibited lesser cytotoxic and inflammatory features and could maintain their exhausted state even after viral clearance.…”
Section: The Time Course Of T Cell Responses In Sars-cov-2 and Hiv-1 Infectionmentioning
confidence: 99%